Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.21037/jgo-21-310
|View full text |Cite
|
Sign up to set email alerts
|

XPA serves as an autophagy and apoptosis inducer by suppressing hepatocellular carcinoma in a PI3K/Akt/mTOR dependent manner

Abstract: Background: To explore the potential biological function of XPA (Xeroderma pigmentosum group A) in hepatic neoplasms and the underlying molecular mechanisms.Methods: Liver cells were used as experimental models to establish HCC (hepatocellular carcinoma) in vitro. Protein extractions were subjected to Western blotting to detect the proteins expression. The lentivirus transfection efficiency was confirmed by Western blot and RT-qPCR, Tunnel staining was used to detect apoptosis, and Transwell assays were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…It is established that the PI3K/Akt/mTOR signaling pathway is implicated in HCC progression [ 15 , 16 , 17 ]. Thus, we examined whether PI3K/Akt/mTOR signaling could be modulated by PSMB5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is established that the PI3K/Akt/mTOR signaling pathway is implicated in HCC progression [ 15 , 16 , 17 ]. Thus, we examined whether PI3K/Akt/mTOR signaling could be modulated by PSMB5.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, it was found out that the downregulation of PSMB5 significantly reduced the phosphorylation level of proteins for the PI3K/Akt/mTOR signaling pathway. A study by Deng et al [16] showed that the overexpression of XPA not only inhibits proliferation, migration and invasion in HCC, but also suppresses the expression of p-PI3K, p-Akt and p-mTOR. Luo et al [17] revealed that YTHDF1 promoted the proliferation of HCC cells by activating the PI3K/Akt/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al showed that the long non-coding RNA RP11-241J12.3 targeting pyruvate carboxylase promotes invasiveness of HCC by disrupting pyruvate metabolism and DNA mismatch repair system ( 38 ). Through the activation of PI3K/Akt/mTOR, XPA suppressed the growth of cancer cells inside the liver by promoting autophagy and cell death ( 39 ). Additionally, a study has found that inhibiting RFX6 through the Notch pathway inhibits the invasive ability of tumor cells and affects tumor immunity in HCC ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…This gene has been shown to promote apoptosis in response to DNA damage, in addition to its role in nucleotide excision repair 29 . Moreover, downregulation of XPA has been associated with decreased patient survival in colorectal cancer 30 .…”
Section: Somatic Mutations In Cleavage and Polyadenylation Signals Ca...mentioning
confidence: 99%